Optimalisasi Pengembangan Sumber Daya Manusia, Kompetensi Dan Kreativitas Terhadap Persepsi Dukungan Organisasi Dan Prestasi Kerja Pegawai Pada Komisi Pemilihan Umum Sebagai Pilar Penyelenggara Pemilu 2029 Yang Efisien Dan Berintegritas Di Kabupaten Sragen - Isnaeni Isnaeni; Aris Tri Haryanto (ProBank, 2026)
The purpose of this study is to test and analyze the results of research related to human resource development strategies, competency, and employee creativity on the perception of organizational support and employee work performance at the General Election Commission of Sragen Regency. The data used are primary data with a sample of 40 respondents of employees at the General Election Commission. The data analysis method was tested with validity tests, reliability tests, partial tests (t-tests), simultaneous tests (F-tests), R-square tests and path analysis tests. The results of the study indicate that: human resource development has a positive and significant effect on the perception of organizational support. Competence has a significant effect on the perception of organizational support. Employee creativity has a significant effect on the perception of organizational support. Human resource development has a significant effect on work performance. Competence has an insignificant effect on work performance. Employee creativity has a positive and significant effect on work performance. Perception of organizational support has a significant effect on work performance. The results of the iF test can be concluded that simultaneously the variables of human resource development, competency, employee creativity, perception of organizational support have a positive and significant effect on employee work performance at the General Election Commission of Sragen Regency. The total R2 is 50.3%. The conclusion of this path analysis shows that the use of the intervening variable of perception of organizational support in order to improve work performance, for the variables of human resource development and employee creativity is ineffective, whereas for competence it is effective.